Analisa Strategi Penerapan Aplikasi “SRIKANDI” (Sistem Informasi Kearsipan Dinamis Terintegrasi) dengan SWOT Analisys terhadap Efektifitas dan Efisiensi Kinerja RSUD Dr. Achmad Mochtar Bukittinggi - Novitrayanti; Alizar Hasan; Perengki Susanto; Hendra Lukito (CV. ALIM'SPUBLISHING, 2026)
Advances in information technology are driving digital transformation in hospital administration, including through the implementation of the Integrated Dynamic Archiving Information System (SRIKANDI) application. Dr. Achmad Mochtar General Hospital in Bukittinggi, as a referral hospital in West Sumatra, has implemented the SRIKANDI application to improve the effectiveness and efficiency of administrative and archival management. However, its implementation still faces various challenges, such as system disruptions, limited internet connectivity, and a lack of staff understanding regarding the application’s use. This study aims to analyze the implementation strategies of the SRIKANDI application regarding the effectiveness and efficiency of performance at Dr. Achmad Mochtar General Hospital in Bukittinggi using SWOT analysis. This study employs a descriptive method with a qualitative approach. Data were collected through observation, interviews, questionnaires, and documentation using source triangulation techniques involving application users, structural officials, and relevant department heads. The results of the study indicate that the SRIKANDI application is capable of increasing the speed of records management, facilitating document retrieval, supporting a paperless system, and enhancing administrative transparency and accountability.The SWOT analysis places the organization in Quadrant II (WO Strategy), which involves leveraging opportunities to address weaknesses. The study’s conclusions indicate that the implementation of the SRIKANDI application has a positive impact on the effectiveness and efficiency of hospital administration; however, improvements in technological infrastructure, ongoing training, outreach, and the development of standard operating procedures (SOPs) are necessary to ensure the application’s implementation runs optimally and sustainably.